INTERNATIONAL EXPERIENCES IN THE FIELD OF LABOR PROTECTION: A COMPARATIVE ANALYSIS - Akhmadbek Jalilov (Web of Journals Publishing, 2024)
In an increasingly interconnected world, the issue of labor protection has become a focal point of global attention. This article undertakes a comprehensive examination of international experiences in labor protection, aiming to identify common practices, challenges, and innovative approaches across diverse contexts. The study employs a comparative analysis of labor protection policies and practices in several key regions, including Europe, North America, Asia, and Africa. By examining legal frameworks, regulatory mechanisms, and enforcement strategies, this research sheds light on the effectiveness and adaptability of different approaches in ensuring the safety, health, and rights of workers. Key findings highlight the role of international conventions and standards, such as those established by the International Labour Organization (ILO), in shaping national policies and fostering cooperation among countries. Furthermore, the study explores the impact of technological advancements and globalization on labor protection, emphasizing the need for agile and responsive regulatory frameworks. Through a synthesis of case studies and empirical data, this article identifies best practices and emerging trends that can inform policymakers, practitioners, and stakeholders in enhancing labor protection at both national and international levels. The insights gleaned from this comparative analysis contribute to ongoing discussions on sustainable development, social justice, and human rights within the global labor landscape. Overall, this research underscores the importance of cross-border collaboration and knowledge exchange in addressing the multifaceted challenges of labor protection. By leveraging international experiences and lessons learned, countries can strive towards more inclusive, equitable, and resilient labor systems in the pursuit of sustainable development goals.
Keywords: labor protection, occupational health and safety, international comparisons, regulatory frameworks, workplace standards, International Labour Organization (ILO), cross-border collaboration, enforcement mechanisms, worker rights, global perspectives.